New Approaches to the Solution of the Problem of the Propagation of Electrical Energy Fluxes in the Material Media and the Long Lines (Global Journal of Science Frontier Research, 2018)
In the article new approaches to the solution of the problem of the propagation of electrical energy fluxes in the material media and the long lines are examined. The electrodynamics of plasma is examined and it is shown that the absolute value of the vector of poytinga can be obtained with the examination of the motion of specific electric field energy and kinetic kinetic energy of the charges, concentrated in the single volumes of plasma. Is obtained wave of equation for the plasma. The electrodynamics of dielectrics is examined and is obtained wave equation for them. Are examined processes occurring in the long lines, filled with plasma or dielectrics and predicted new phenomenon transverse plasma resonance in the limited nonmagnetized plasma. The use of transverse plasma resonance opens the possibility of designing of the lasers of large power.
Keywords: maxwell's equation; wave equation; poynting's vector; plasma; dielectric; plasma resonance; transverse plasma resonance; long line; laser